2012
DOI: 10.1002/jbm.a.34215
|View full text |Cite
|
Sign up to set email alerts
|

Improved osteoblast compatibility of medical‐grade polyetheretherketone using arc ionplated rutile/anatase titanium dioxide films for spinal implants

Abstract: Titanium dioxide (TiO(2)), known to exhibit good biocompatibility, is applied in this study as a thin film formed onto polyetheretherketone (PEEK) substrate, which has been widely used in spinal interbody fusion cages. For successful deposition, an arc ionplating (AIP) technique was applied to deposit TiO(2) at low deposition temperature without damaging PEEK substrate, while providing satisfactory film adhesion. This study systematically investigates the effects of TiO(2) thin film phase composition and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 31 publications
(64 reference statements)
1
40
0
Order By: Relevance
“…These three indicators confirmed the osteoblast compatibility of the TiO 2 -coatings deposited on PEEK. Furthermore, the osteogenesis performance (revealed by OPN, OCN, and calcium content as shown in Figure 6(d)-(f) [36], respectively) demonstrated that TiO 2 coatings also significantly increased the osteogenesis performance. This suggests that TiO 2 coatings enhance extracellular bone matrix growth.…”
Section: In Vitro Characteristics Of Tio 2 -Coated Peekmentioning
confidence: 87%
See 4 more Smart Citations
“…These three indicators confirmed the osteoblast compatibility of the TiO 2 -coatings deposited on PEEK. Furthermore, the osteogenesis performance (revealed by OPN, OCN, and calcium content as shown in Figure 6(d)-(f) [36], respectively) demonstrated that TiO 2 coatings also significantly increased the osteogenesis performance. This suggests that TiO 2 coatings enhance extracellular bone matrix growth.…”
Section: In Vitro Characteristics Of Tio 2 -Coated Peekmentioning
confidence: 87%
“…Next, the cell morphology that had attached to the PEEK and TiO 2 -coated PEEK specimens was observed using field emission scanning electron microscopy (FESEM; Hitachi S-4800). Figure 6 shows the osteoblast cell adhesion ability, cell proliferation ability, cell differentiation ability, and osteogenesis performance on the PEEK and TiO 2 -coated PEEK specimens at various deposition conditions [36]. Notably, the osteoblast cell adhesion, proliferation, and differentiation abilities on TiO 2 -coated PEEK specimens were superior to the bare PEEK specimens for all of the deposition conditions.…”
Section: In Vitro Characteristics Of Tio 2 -Coated Peekmentioning
confidence: 99%
See 3 more Smart Citations